CULTURAL RESONANCE: PARALLELS AND DIVERGENCES IN UZBEK AND ENGLISH HEROIC EPICS - Rayimkulova Laylo Otabek qizi (KONFERENSIYALAR, 2025)
Annotation.  This  article  investigates  the  people  courageous  legends  of  Uzbekistan  and Britain,  highlighting  both  the  parallels  and  divergences  in  their  story  structures,  topical components,  and  social  importance.  Through  a comparative  investigation,  we  look  at  how  these legends  reflect  the  interesting  verifiable  settings,  societal  values,  and  ethical  lessons  of  the individual societies. By analyzing unmistakable works such as “Alpomish” from Uzbek old stories and  “Beowulf”  from  English  convention,  we  reveal  how  each  epic  serves  as  a  vessel  of  social personality and communal values. This consider points not as it were to improve the understanding of these courageous accounts but too to demonstrate the all inclusive topics of mettle, honor, and the human encounter that rise above social boundaries.